2000
DOI: 10.1046/j.1365-2826.2000.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Rat Adrenal Transplants are Reinnervated: An Invalid Model of Denervated Adrenal Cortical Tissue

Abstract: Adrenal autotransplantation is a widely used approach to investigate the potential for neural modulation of adrenal cortical function. It is believed that regenerating adrenal transplants are not reinnervated, thereby providing a model to investigate adrenal function in the absence of neural modulation. However, the hypothesis that adrenal transplants become reinnervated has not been directly tested. The purpose of the present study was to characterize the time course, extent, and nature of the reinnervation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…These findings are similar to those of auto-or syngeneic transplants of other organs and tissues in experimental animals. For example, sympathetic efferent reinnervation is commonly observed in transplants of the parathyroid gland (21), pancreatico-duodenum (22), lung (23), heart (24), and adrenal gland (25). Sensory innervation, although not studied as often, is also observed, for example in transplants of lung (26,27) and heart (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to those of auto-or syngeneic transplants of other organs and tissues in experimental animals. For example, sympathetic efferent reinnervation is commonly observed in transplants of the parathyroid gland (21), pancreatico-duodenum (22), lung (23), heart (24), and adrenal gland (25). Sensory innervation, although not studied as often, is also observed, for example in transplants of lung (26,27) and heart (28).…”
Section: Discussionmentioning
confidence: 99%
“…Sensory innervation, although not studied as often, is also observed, for example in transplants of lung (26,27) and heart (28). Sensory innervation is sometimes sparse, for example in transplants of the parathyroid and adrenal glands (21,25), and may relate to the site of implantation as noted by Korsgren et al (29), who found that the extent of sensory reinnervation of pancreatic islet cells was markedly different for implants in the spleen, liver, or renal subcapsule.…”
Section: Discussionmentioning
confidence: 99%
“…To control for the transplantation procedure, WT animals received their own (i.e., WT) adrenal transplants following adrenalectomy. After the surgery, animals were allowed to recover for 8 weeks under standard LD conditions to ensure complete reinnervation of the transplanted tissues (66).…”
Section: Methodsmentioning
confidence: 99%
“…While adrenal cell transplantation into the subcapsular region of the kidneys leads to good regeneration of adrenal cortical tissue, cell transplantation into the skin has also been reported to be possible when a collagen gel is used [29]. Although previously denied, autologous transplantation of adrenocortical cells or tissues does actually cause innervation, which is correlated with the degree of recovery of the steroid production [30]. Crawford et al demonstrated that stable SF-1 expression in ESCs resulted in a steroidogenic capacity and adenosine 3,5-cyclic monophosphate (cAMP) or retinoic acid-dependent inducibility of cytochrome P450scc, leading to progesterone production [31].…”
Section: Transplantation Regeneration and Gene Therapy For The Adrenmentioning
confidence: 99%